International Liaison Committee on Resuscitation: COVID-19 consensus on science, treatment recommendations and task force insights. (June 2020) - Perkins, G.D.; Morley, P.T.; Nolan, J.P.; Soar, J.; Berg, K.; Olasveengen, T.; Wyckoff, M.; Greif, R.; Singletary, N.; Castren, M.; de Caen, A.; Wang, T.; et al.
Abstract: Consensus on Science and Treatment recommendations aim to balance the benefits of early resuscitation with the potential for harm to care providers during the COVID-19 pandemic. Chest compressions and cardiopulmonary resuscitation have the potential to generate aerosols. During the current COVID-19 pandemic lay rescuers should consider compressions and public-access defibrillation. Lay rescuers who are willing, trained and able to do so, should consider providing rescue breaths to infants and children in addition to chest compressions. Healthcare professionals should use personal protective equipment for aerosol generating procedures during resuscitation and may consider defibrillation before donning personal protective equipment for aerosol generating procedures.